Prolonged use of cough formulations and the health risk from their antimicrobial activity on some normal bacterial flora (2010)
Cough formulations were observed to contain some chemical substances that have been associated with antimicrobial property, namely: menthol, honey, citric acid and volatile oils. A prolonged use of such formulations by patients was therefore considered a health risk on the normal bacterial flora. Nine cough formulations denoted by letter codes along with simple syrup B.P., absolute alcohol and sterile distilled water as controls, were investigated for relative antimicrobial activity on some normal flora bacteria by the agar-cup diffusion method. The respective individual single brands of cough formulation with the exception of one brand exhibited inhibitory activity against 5 - 1 2 bacterial isolates including Escherichia coli, Klebsiella spp, Streptococcus faecalis, Strep. pneumoniae, Strep. viridians, Proteus mirabilis, Staphylococcus aureus and Pseudomonas aeruginosa. Simple Syrup B.P. and sterile distilled water did not exhibit any antibacterial activity while the absolute alcohol exerted activity only on Staph aureus. The antimicrobial activity recorded for the cough formulations could cause a depletion of the normal bacterial flora following a prolonged use of the formulations tested, hence, the attendant health risk of depressed natural immune system of the body, normally associated with such bacteria. pathological status when it presents as a